КАК СПРАВИТЬСЯ С КУЛЬТУРНЫМ ШОКОМ? - Менлимуратова, Э.А. (SCIENCE and SOCIETY, 2025)
This article discusses culture shock, the essence of which is the clash between a person’s usual values, norms of behavior, language, and everyday customs characteristic of his previous society, and the values, norms, language and everyday practices inherent in a new, alien cultural environment in which he finds himself. Culture shock is experienced by everyone who finds himself in an unfamiliar cultural environment for the first time.